4(2x-3)-7x+5=11

Simple and best practice solution for 4(2x-3)-7x+5=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-3)-7x+5=11 equation:


Simplifying
4(2x + -3) + -7x + 5 = 11

Reorder the terms:
4(-3 + 2x) + -7x + 5 = 11
(-3 * 4 + 2x * 4) + -7x + 5 = 11
(-12 + 8x) + -7x + 5 = 11

Reorder the terms:
-12 + 5 + 8x + -7x = 11

Combine like terms: -12 + 5 = -7
-7 + 8x + -7x = 11

Combine like terms: 8x + -7x = 1x
-7 + 1x = 11

Solving
-7 + 1x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 1x = 11 + 7

Combine like terms: -7 + 7 = 0
0 + 1x = 11 + 7
1x = 11 + 7

Combine like terms: 11 + 7 = 18
1x = 18

Divide each side by '1'.
x = 18

Simplifying
x = 18

See similar equations:

| 4x+2x+9+x+4=34 | | (2x+2)(3x^2-x+2)= | | -3(1)-3= | | y=[100+.75(y-100)]+100+100 | | -8s+32=54 | | .66x+7=39 | | -9s+14=21 | | 2.4=0.3x+0.4y | | 2(3x+5)=5(x-4)-(5-3x) | | 12x+7c=315 | | (4x+2)(6-3x)= | | 400=x^2+42x | | 0=18x^2+90x-432 | | z6y4/z6y5 | | X^2-10x+20=8 | | a/6=7=11 | | -4s+30= | | -6z+12=24 | | -14-5n=2(5n+7)+5n | | (2x+3y)dx+(y+2)dy=0 | | -4s+15=25 | | (4x+2)+(5x-7)+3x=180 | | (2x-1)(5x^2+6x-3)= | | y^3+y=50 | | tanx=1.274 | | 187x=374 | | (2w^2-3w+1)(4w^2-7w-2)= | | 12=x+9-5x | | X+(-11)=13 | | x^2+y^2=1 | | (7x^2-5x-3)(2x+4)= | | X-(-9)=24 |

Equations solver categories